2012
DOI: 10.1614/ipsm-d-11-00048.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management of Scotch Broom (Cytisus scoparius) Using Biological Control

Abstract: Integrated weed management strategies (IWM) are being advocated and employed to control invasive plants species. In this study, we compared three management strategies (biological control alone [BC], BC with fire [BC + F], and BC with mowing [BC + M]) to determine if physical controls reduce seed production by Scotch broom and interfere with the action of the biological control agent—the Scotch broom seed weevil. We measured seed production and seed predation by the weevil at both pod and plant scale, and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Cytisus striatus (Hill) Rothm. is a shrubby legume endemic to the Iberian Peninsula that has colonized other parts of the world [ 28 ]. It grows in siliceous soils from 450–750 m a.s.l., avoiding cold distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Cytisus striatus (Hill) Rothm. is a shrubby legume endemic to the Iberian Peninsula that has colonized other parts of the world [ 28 ]. It grows in siliceous soils from 450–750 m a.s.l., avoiding cold distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, post-dispersal seed predation has the potential to filter the species pool available for recruitment of the woody community in a similar way in all landscape units, irrespective of the degree of degradation, reducing the number of propagules of dominant tree species and favouring further a shrub-like landscape, which is the type of landscape unit where rodents can find both food and refuge [26], [37]. Although we do not have data on seed predation in dry-fruited shrubs (mainly ballistic dispersal) in our study area, other studies indicate that their predation is much lower than for tree species, and are especially depredated by weevils before dispersal and by ants afterwards [38][41].…”
Section: Resultsmentioning
confidence: 85%
“…Since seasonal sensitivities increase in the spring and allergic reactions occur in sensitive people, especially children and the elderly, investigating allergenicity of the pollen grains and aromatic petalsin plants that pollinatein the spring is necessary. Because the pollen grains of this plant are carried by bumblebees and wasps (21,24), it is possible that pollen grains containing allergen compounds used in honey production can enter the human body (8,25). Our research in 2014, showed allergenicity petals of old ontogenical (26).…”
Section: Introductionmentioning
confidence: 86%
“…This beautiful and extremely fragrant flower is native to Europe and North Africa and has subsequently spread to Asia (18)(19)(20). The flowering period is between the months of May and June (19)(20)(21)(22)(23)(24). Since seasonal sensitivities increase in the spring and allergic reactions occur in sensitive people, especially children and the elderly, investigating allergenicity of the pollen grains and aromatic petalsin plants that pollinatein the spring is necessary.…”
Section: Introductionmentioning
confidence: 99%